Performance of Wind Power Plant in West Kalimantan, Indonesia - Kurnianto, Rudi; Setiawati, Firsta Zukhrufiana; Sanjaya, Bomo Wibowo; Gianto, Rudy; Panjaitan, Seno Darmawan; Nugraha, Ananggirieza (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2020)
The aim of this paper is threefold. First, to calculate the correction factors based on existing meteorological station positions and its extension according to the basic map of West Kalimantan. Second, to reanalysis, the wind speeds from satellite measurements of national oceanic, and atmospheric administration (NOAA) and physical sciences division (PSD) in West Kalimantan by calculating its resultant and applying correction factor to create a map of wind power potential in West Kalimantan. Last, to apply the highest corrected wind speeds using HOMER simulation to know the wind energy potential. Conclusions have extracted the characteristics of wind speed variability over West Kalimantan, and HOMER simulation results of the highest wind speed.